2003
DOI: 10.1007/s00441-002-0654-4
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-concentrating hormone system in the brain and skin of the cichlid fish Cichlasoma dimerus : anatomical localization, ontogeny and distribution in comparison to α-melanocyte-stimulating hormone-expressing cells

Abstract: Distribution and development of the melanin-concentrating hormone (MCH) system were examined by immunocytochemistry of the brain, pituitary gland and skin of the South American cichlid fish Cichlasoma dimerus. In adults, the most prominent group of MCH-ir perikarya was located in the nucleus lateralis tuberis (NLT). Outside the NLT, in the posterior hypothalamic region, a group of small neurons was found between the third ventricle and the lateral ventricular recess with delicate immunoreactive fibers that did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, the latter study did not describe the presence of MCH-producing cells associated to the PVO within the caudal hypothalamus but immunoreactive cell bodies were reported within the zona limitans. Similar MCH-mRNA-expressing cell clusters have been previously reported in several teleost species including rainbow trout [35], cichlid fish, Cichlasoma dimerus [7], tilapia [4], barfin flounder [6] gilthead seabream [5] and eel [36]. Hypothalamic-hypophyseal neurons in the lateral tuberal nucleus respond strikingly to background color changes and constitute the most prominent MCH-mRNA-expressing cell cluster in the teleost brain [36].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, the latter study did not describe the presence of MCH-producing cells associated to the PVO within the caudal hypothalamus but immunoreactive cell bodies were reported within the zona limitans. Similar MCH-mRNA-expressing cell clusters have been previously reported in several teleost species including rainbow trout [35], cichlid fish, Cichlasoma dimerus [7], tilapia [4], barfin flounder [6] gilthead seabream [5] and eel [36]. Hypothalamic-hypophyseal neurons in the lateral tuberal nucleus respond strikingly to background color changes and constitute the most prominent MCH-mRNA-expressing cell cluster in the teleost brain [36].…”
Section: Discussionmentioning
confidence: 66%
“…This central accumulation of the pigmentary organelles results in a change in the refractive index making the scales appear paler, thus allowing cryptic camouflage [2]. MCH neurons in the rostral hypothalamus of teleost fish have also been shown to project into the adenohypophysis modulating the secretory activity of cells producing ACTH, melanocyte-stimulating hormone (MSH) and somatolactin (SL) [2,3,4,5,6,7]. In addition to skin color regulation, MCH has been suggested to be involved in stress responses [8, 9], osmoregulation [10], water acidification [9] and food intake in teleost fish.…”
Section: Introductionmentioning
confidence: 99%
“…Results from C. dimerus indicate that the mechanisms by which adaptation takes place must be present early in larvae stages. By 15 dph, the hypothalamic neuropeptide melaninconcentrating hormone (Mch), the pars intermedia pituitary hormones melanocyte-stimulating hormone (Msh) and Sl are already being expressed in C. dimerus (Pandolfi et al, 2001(Pandolfi et al, , 2003 hormones that have been demonstrated to regulate both morphological and physiological changes in adult fish (Cánepa et al, 2006(Cánepa et al, , 2012Sköld et al, 2016;Sugimoto, 2002;Zhu and Thomas, 1997). This co-occurrence in time between background adaptation and the presence of these hormones shows that skin pigmentation-regulating mechanisms are active from an early stage of development.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of MCH has been examined in Pleuronectiformes (Baker and Bird, 2002; Amano et al, 2003; Amiya et al, 2008a, b), Cyprinodontiformes (Batten and Baker, 1988; Batten et al, 1999) and Perciformes (Mancera and Fernández-Llebrez, 1995; Batten et al, 1999; Duarte et al, 2001; Baker and Bird, 2002; Pandolfi et al, 2003; Cánepa et al, 2008). The overall distribution of MCH neurons remains mostly the same, with the main group of cells found in the NLT and a second, smaller group found close to the LVR (Figure 3).…”
Section: The Mch System In the Ray-finned Fish Lineagementioning
confidence: 99%
“…In S. auratus , cells were found in the periventricular area of the medial hypothalamus from days 4 through 23 after hatching, disappearing after this time frame (Mancera and Fernández-Llebrez, 1995). In C. dimerus , the transient neurons were found in the nucleus periventricularis posterior, starting at day 6 and disappearing by day 42 after hatching (Pandolfi et al, 2003).…”
Section: The Mch System In the Ray-finned Fish Lineagementioning
confidence: 99%